Моделирование и оценка эксплуатационных характеристик шарошечных калибраторов в стволе наклонной скважины - Гасанов, Р.А.; Ширали, И.Я.; Амиров, Р.Г.; Волков, А.С. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
Methodic for calculating to the strength main elements of calibration is elaborated. Observed that the nominal diameter of inclined wells in the given drilling column riding collection by the roller gagger ensured completely lets down casing column before project depth